Automation in drip irrigation system for cotton growing on large scale - a case study - Taley, S. M., author; Patode, R. S., author; Mankar, A. N., author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2002)
Micro Irrigation technology concept is now accepted by most of the farmers in Maharashtra. Its adoption started in grapes a decade back and has since then spread into a large number of crops. Drip irrigation however had not been adopted in cotton crop until as recently as four to five years ago. This was primarily because cotton has a large plant population. Adequate research recommendations are not available regarding net water requirement, plant population, plant to plant and row to row spacing, distance between emitters, emitters discharge in black cotton and light soils etc. However, as progressive farmers tried drip irrigation in cotton with remarkable success. Fertigation through drip is yet to be given a genuine attempt. An integrated pest management approach to plant protection in cotton is a recent attempt in organized scale cluster demonstration and farmer's field school. Drip irrigation offers additional advantages in cotton growing such as application of controlled quantity of water at the initial stages of plant propagation in order to increase flowering, earl in flowering and thus higher yields and at source fertigation. Water saving of 60 percent increase in the irrigated area, and reduces the cost of fertigation, weeding, etc. This paper deals with the irrigation system equipment, design layout, computer control, field communication systems and water requirements.
USCID/EWRI conference
Not digitized by CSUL Digital Services.
Presented at the 2002 USCID/EWRI conference, Energy, climate, environment and water - issues and opportunities for irrigation and drainage on July 9-12 in San Luis Obispo, California.